Associations between patient-reported vision impairment in low luminance and vision-related quality of life in intermediate age-related macular degeneration - Terheyden, Jan H.; Gittel, Lisa; Wu, Zhichao; Guymer, Robyn H.; Finger, Robert P. (Scientific reports, 2025)
Intermediate age-related macular degeneration (iAMD) reduces vision under low-luminance conditions, affecting quality of life (QoL). The Vision Impairment in Low Luminance (VILL) questionnaire captures QoL domains relevant in iAMD but most AMD studies use the generic vision-related QoL measure Visual Function Questionnaire (NEI VFQ). To investigate associations between these generic and specific vision-related QoL instruments, and explore the added value of including the VILL over the NEI VFQ in future iAMD studies, we analysed cross-sectional study data from individuals with iAMD. Associations were investigated using age-adjusted regression models. We included 150 participants (73% women, 74.6 ± 7.8 years). VILL subscale scores were associated with NEI VFQ scores (p ≤ 0.014) and explained 62.0% to 67.9% in the variance of the NEI VFQ scores. Ceiling effects were more common in the visual functioning NEI VFQ subscale than in the VILL-Reading subscale (p = 0.039), while the emotional well-being scores did not differ signficiantly between the instruments. NEI VFQ scores, VILL-Reading and VILL-Mobility subscale scores were associated with best-corrected visual acuity in either eye. Thus, assessments of vision-related QoL in iAMD using a generic instrument and a low luminance vision-specific instrument yield comparable but not identical results. The VILL has less ceiling effects than the NEI VFQ, suggesting its suitability for iAMD intervention trials and added value over the NEI VFQ in populations with few functional deficits.